Nursing educator perspectives of overseas qualified nurses' intercultural clinical communication: barriers, enablers and engagement strategies. Issue 17 (3rd June 2015) - Philip, Susan; Manias, Elizabeth; Woodward‐Kron, Robyn
<x xml:space="preserve">Abstract</x> Aims and objectives To understand the intercultural communication experiences and associated communication training needs of overseas qualified nurses in the Australian healthcare system from the unique perspectives of nurse educators teaching in accredited bridging programmes. Background Overseas qualified nurses are an integral part of the nursing workforce in migration destination countries. Communication training needs are more complex when there are cultural, ethnic and language differences between nurses, other health professionals and patients. Design A qualitative, exploratory research design using semi‐structured interviews. Methods All (nine) organisations involved in conducting the Australian Health Practitioner Regulation Agency approved preregistration bridging programmes for overseas qualified nurses within the state of Victoria, Australia, were involved in the study. Participants were 12 nurse educators employed in these organisations. Thematic analysis was undertaken. Results Three macro themes emerged about the overseas qualified nurses' intercultural communication: (1) pre‐existing barriers and enablers to intercultural communication, for example, nurses' reluctance to engage in communicative strategies that build rapport with patients, (2) transitional behaviours and impact on communication, including maintenance of perceived cultural hierarchies between health professionals and (3) development of communicative competence, including expanding one's repertoire of conversational gambits. Conclusions The findings point to the domains and causes of communication challenges facing overseas qualified nurses in new healthcare settings as well as strategies that the nurse educators and nurses can adopt. Communication cannot be merely regarded as a skill that can be taught in a didactic programme. Comprehensive understanding is needed about the sociocultural dimensions of these nurses' orientation, which can impact on how they communicate in their new healthcare settings. Relevance to clinical practice The findings can act as triggers for discussion with overseas qualified nurses and other health professionals to raise awareness about the aspects of intercultural communication and to debate alternative viewpoints and explanations. They can also inform changes in the structure and content of the bridging programmes.